DEVELOPING SUBJECT-SPECIFIC PEDAGOGY THROUGH PROJECT-BASED LEARNING: ENHANCING PRESERVICE SCIENCE TEACHERS' PERFORMANCE - Tyas, Rizki Arumning; Wilujeng, Insih; Rosana, Dadan; Anjarsari, Putri (Jurnal Pendidikan Matematika dan IPA, 2026)
Preparing preservice science teachers for future teaching requires learning approaches that strengthen pedagogical competence while integrating scientific knowledge with authentic classroom practices. Project-based learning offers such an approach by promoting active engagement and meaningful professional experiences. This study aimed to examine the contribution of project-based learning to the development of science subject-specific pedagogy among preservice science teachers. This study employed a pre-experimental one-shot post-test design. Participants completed a project-based learning program over eight instructional meetings and subsequently responded to a 10-item questionnaire measuring learning quality, motivation, and performance. The data were analyzed using descriptive statistics, supported by responses to open-ended questions. The results showed that learning quality (M = 4.38) and motivation (M = 4.28) were categorized as very good, while performance (M = 4.18) was categorized as good. These findings indicate that project-based learning contributes positively to preservice science teachers' ability to develop science subject-specific pedagogy by strengthening conceptual understanding, enhancing pedagogical competence, and fostering creativity and innovation in instructional design.